Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) as inflammatory biomarker in cystic fibrosis - Ehab Mohamed Mohamed Alahwal; Hanan Ali Madani; Hanan Mohsen Osman; Noussa Ragab Mohamed (Cairo : Ehab Mohamed Mohamed Alahwal, 2018)
Cystic fibrosis (CF) is an autosomal recessive disease with significant associated morbidity and mortality. A cross sectional study included 60 patients diagnosed as cystic fibrosis (CF) age and sex matched with 30 healthy children as control group. Thirty-seven (61.7%) patients were males and 23 (38.3%) were females. Serum samples of patients collected from cystic fibrosis clinic in specialized Children Hospital, Cairo University, to detect serum levels of sTREM-1. HRCT chest was done and brody score was used to evaluate the degree of lung affection in CF cases. There was significant elevation of (sTREM-1) in the plasma of CF patients than healthy control group (P value = 0.001) but no significant difference in level of (sTREM-1) between stable and exacerbated CF patients (P value =1). In this study there was no correlation between sTREM-1 levels and HRCT scoring (P=0.903) and no correlation between sTREM-1 and CRP (P=0.445). This study demonstrated significant trends for progression of severity of lung disease with increasing patient age (p < 0.05) regarding overall CT brody score
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Cystic fibrosis; High resolution computerized tomografy; Sweat chloride